INFLUENCE OF ALLOGENEIC STEM CELLS ON CHANGES OF SYNOVIAL FLUID IN THE KNEE JOINT OF RABBITS AT EXPERIMENTAL OSTEOARTHROSIS - Demiantseva, Yu. V. (Scientific Progress & Innovations, 2020)
The article presents the results of analyzing synovial fluid in rabbits with simulated osteoarthrosis using allogeneic stem cells and the traditional method of treatment (using meloxicam). Three groups of animals were formed: control group – isotonic sodium chloride solution was applied; the first experimental group – the traditional method of treatment was used; the second experimental group – allogeneic mesenchymal stem cells were used. A model of osteoarthritis of the knee joint was reproduced on animals of three groups by double injecting retinol acetate into the joint cavity – 3.44 % at a dose of 1 ml with an interval of 7 days. Synovial fluid of animals was taken on the 7th, 14th and 28th days after the last administration of prepara-tions. It was found that under traditional treatment inflammatory process was more pronounced than in oth-er groups, but the number of foamy macrophages, and then synoviacytes was reduced. It may indicate the inhibitory effect of non-steroidal anti–inflammatory preparation (meloxicam), which was used in treatment. A similar situation was registered in the control group, only all stages were slower than in the first and sec-ond experimental groups. With introducing AMSC – the number of synoviocytes in the synovial fluid was much higher (on the 14th day), which indicated accelerated differentiation of synoviacytes. An increased number of foamy macrophages (more active process of fat droplets resorption) were detected. On the 28th day, areas of synovial cells accumulation in the synovia and completion of the inflammatory process were observed. In the synovial fluid aspirate in all groups of rabbits, it was found that the repair process took place: from the beginning there was a large number of fat droplets (after introducing retinol acetate at the stage of osteoarthritis simulation), which activated macrophages to absorb and utilize the fat droplets; after that cellularity sharply decreased, but the number of synoviacytes increased. Thus, according to the re-search, local administration of allogeneic mesenchymal stem cells under experimental knee joint osteoarthri-tis increases the activity of recovery processes, as it is evidenced by the increased number of synoviocytes in the synovial fluid and accelerated completion of the inflammatory process.